Insight : uma abordagem guiada pela informação para análise qualitativa com suporte de visualização e mineração de texto - Hernandes, Elis Cristina Montoro (2014)
Usually, experimental studies that are conducted to generate evidences on the different scientific fields produce many qualitative data to be analyzed by researchers. For instance, this is the case of defects lists generated from the software inspection activity, which defects consist of qualitative data that should be discussed and classified. This scenario was experienced during the Readers Project, where defects lists have token long time to be analyzed, sometimes hours or days, making the decisions about defects difficult. Moreover, feedback questionnaires deserved a careful analysis, since they carried relevant information about the experimental study. Aim: Driven by the described situation this research aimed to support the qualitative analysis conduction in an information-guided way, using visualization and text mining techniques to enable it. This approach allows software inspection defects described similarly be analyzed together, due to the use of these techniques, which may allow the homogeneity of the decisions about them. The same happens in the context of feedback questionnaires. Methodology: Based on the objective, the ways that visualization and text mining could contribute to become qualitative analysis more effective and efficient were investigated and designed. Considering it, the Insight tool was developed to enable the information-guided qualitative analysis. Experimental studies were conducted to validate and evaluate the approach on different contexts. Results: Four experimental studies were conducted: (i) a feasibility study conducted with text documents which gave evidences that the use of visualization and text mining met previous expectations and was feasible to be employed; (ii) a study in the context of software inspection which, although the quantitative data did not present statistical significance, the descriptive statistics and feedback questionnaires analysis gave evidences that visualization and text mining makes the qualitative analysis effective and efficient; (iii) a study in the context of questionnaires, which results were similar to the previous study; (iv) a case study in the context of qualitative analysis of long text documents which gave evidences about the utility and ease of use of the approach. Conclusion: Under the different contexts of evaluation, the Insight, an information-guided qualitative analysis approach that is based on visualization and text mining, gave evidences about the improvements on efficiency and effectiveness. Adding to its relevance in software engineering area, this research also contributes to other scientific fields, which often claim for technological support to conduct their research.